Photocurable acrylate epoxy/ZnO–Ag nanocomposite coating: fabrication, mechanical and antibacterial properties. Issue 36 (17th August 2022) - Nguyen, Thien Vuong; Do, Truc Vy; Ngo, Thanh Dung; Nguyen, Tuan Anh; Lu, Le Trong; Vu, Quoc Trung; Thi, Lan Pham; Tran, Dai Lam
Abstract : ZnO-Ag hybrid nanoparticles were fabricated by seed-mediated growth method and incorporated into the UV-curable acrylate resin matrice to form a composite. This improved the mechanical property of UV-cured coating and exhibited high antibacterial activity against E. coli . Abstract : In this study, a UV-curable acrylate epoxy nanocomposite coating has been prepared by incorporation of ZnO–Ag hybrid nanoparticles. For this purpose, firstly ZnO–Ag hybrid nanoparticles were fabricated by a seed-mediated growth method. Then, these ZnO–Ag hybrid nanoparticles (2 wt%) were added into the UV-curable acrylate resin matrices. The photocuring process of nanocomposite was evaluated by various factors, such as the conversion of acrylate double bonds, pendulum hardness and gel fraction. Under the 4.8 s UV-exposure time for full crosslinking, the obtained data indicated that incorporation of ZnO–Ag nanohybrids into the coating matrix changed the crosslinking process of coating significantly. A mechanical teat indicated that the presence of nanohybrids in photocurable coating matrix enhanced its abrasion resistance from 98.7 to 131.6 L per mil (33.3%). The antibacterial test against E. coli over 7 h indicated that E. coli bacteria were killed totally by nanocomposite coating, whereas it was 2.6 × 10 4 CFU mL −1 for the neat coating without nanoparticles.